2022
DOI: 10.14740/jocmr4691
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between ABO Blood Group and the Risk of Colorectal Cancer: A Retrospective Multicenter Study

Abstract: Background: Colorectal cancer (CRC) is the fourth deadliest cancer, with approximately 900,000 deaths annually. CRC is a multifactorial disease in which a set of factors, including environmental, hereditary, and genetic factors, are integrated into cancer development.Studies have suggested an association between hereditary antigens in the human blood group system and the risk of different cancers. This study aimed to evaluate the relationship between blood groups and CRC risk. Methods:A record-based retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…For instance, Abdullah Al-Sawat et al found a statistically significant link between colon cancer and blood groups of AB and non-O when compared to the O blood group. [15] Other studies have also demonstrated that blood type AB is a sufficient risk factor for individuals with colon cancer. [16] Additionally, large research found that individuals with blood type B had a statistically significant decreased risk of gastrointestinal malignancies, but those with blood type AB had a higher risk of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Abdullah Al-Sawat et al found a statistically significant link between colon cancer and blood groups of AB and non-O when compared to the O blood group. [15] Other studies have also demonstrated that blood type AB is a sufficient risk factor for individuals with colon cancer. [16] Additionally, large research found that individuals with blood type B had a statistically significant decreased risk of gastrointestinal malignancies, but those with blood type AB had a higher risk of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Few laboratory studies have proposed various possible mechanisms for the observed relationships between ABO blood types and cancer, such as immunological defense against cancerous cells, intercellular adhesion, and membrane signaling. [14][15][16] A recent study suggested a possible association between ABO blood groups and the likelihood of having CRC. [17] Blood group antigens are present on the outer layer of erythrocytes and other tissues, such as epithelial cells of the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the ABO blood group antigens could in uence tumorigenesis by changing intercellular adhesion, membrane signaling and immune surveillance 20 . Some studies have reported the lack of association between ABO blood groups and CRC, Khalili et al found no signi cant association between blood group B and the overall risk of colon cancer 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Levels of gut microbiome such as Faecalibacterium and Bacteroides are associated with ABO genes and blood antigens are used as a preferred source of energy in the intestine 13 . However, only a few studies have assessed the association between ABO blood groups and CRC risk, and they did not distinguish between bowel cancer subtypes 14,15 . Thus, it is necessary to recognize the blood groups based on molecular characteristics to guide the individualized treatment of SRCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…observations of colorectal cancer (crc) association with aBo blood groups are contradictory. some researchers have found that certain aBo blood phenotypes could be associated with a higher incidence of crc (5)(6)(7)(8)(9), while other researchers have found no association (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 97%